Diplotaxis tenuifolia (L.) DC., a source of a potentially antifungal essential oil containing nitrile - Rodriguez, Silvana Andrea (2006)
Diplotaxis tenuifolia (L.) DC., commonly known in Argentina as “Flor amarilla”, belongs to the Brassicaceae family. Aerial parts of D. tenuifolia were collected in March 2004, at Bahía Blanca city, Buenos Aires province, Argentina, and subjected to hydrodistillation.The major constituent (91 %) of the oil was identified as 5-methylthiopentanenitrile by GC-M and 1H and 13C NMR spectra. The antifungal activity of the distilled oil was evaluated by the paper disk-agar diffusion method against Penicillium digitatum, Penicillium funiculosum, Fusarium oxysporum, Phytophthora infestans and Rhizopus sp. A moderate antifungal activity was observed against Phytophthora infestans, Penicillium digitatum and Penicillium funiculosum. The detection of 5-methylthiopentanenitrile provides evidence for the occurrence of 4-methylthiobutylglucosinolate in D. tenuifolia.